"Once upon a story": Entering into the world of stories to exp-lore the imaginary and (re)living-through experiences of children - Balsawer, Veena (University of Ottawa (Canada), 2010)
Reading is a transaction, a two-way process, involving a reader and a text at a particular time under particular circumstances (Rosenblatt, 1982). An interest in working with children, and an intrigue in the ways children transact with the stories they hear and/or read has turned me into a "Storycatcher" (Baldwin, 2005). As a storycatcher-researcher, I ventured into the world of stories at the Ottawa Public Library in order to exp-lore the narrative transactions of children between the ages of 3 and 6 years old. My Storycatching is a narrative within a narrative because my focus is on the four (4) child-storytellers' verbal and pictorial narratives, as they embody the literary transactions between themselves, their imaginations, and their live(d) experiences in response to the stories they hear during storytimes at the library.
Keywords: Education, Reading.